2015
DOI: 10.3892/ol.2015.3731
|View full text |Cite
|
Sign up to set email alerts
|

Successful multimodal therapy for an α-fetoprotein-producing gastric cancer patient with simultaneous liver metastases

Abstract: Abstract. α-fetoprotein-producing gastric cancer (AFPGC) is considered to be a special type of stomach cancer, due its features of high malignancy, fast progression, easy transferral and a poor prognosis. No standard therapy is currently available for patients with AFPGC. In the present study, the case of a 59-year-old male diagnosed with AFPGC and simultaneous liver metastases is presented. The patient presented with abdominal bloating and multiple liver lesions were revealed upon imaging. During the course o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…Similarly, in our present study, we also found that serum AFP in one patient decreased from 2000 ng/mL to 400 ng/mL with apatinib. Also, multi-target tyrosine kinase inhibitors, including sorafenib, which was approved for first-line treatment of HCC, were reported to be effective for this type of GC[ 28 ], indicating a correlation between the carcinogenesis of AFPGC and HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in our present study, we also found that serum AFP in one patient decreased from 2000 ng/mL to 400 ng/mL with apatinib. Also, multi-target tyrosine kinase inhibitors, including sorafenib, which was approved for first-line treatment of HCC, were reported to be effective for this type of GC[ 28 ], indicating a correlation between the carcinogenesis of AFPGC and HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Since VEGF and VEGF-C serve as angiogenic factors in the tumor microenvironment (22), their inhibition may exhibit anti-angiogenic and anti-tumor activities on AFPGC. However, only a few cases of the efficacy of an anti-angiogenic multi-kinase inhibitor (namely sorafenib) in AFPGC patients have been reported thus far (23,24). The clinical efficacy of ramucirumab, a monoclonal antibody for VEGF receptor-2, in AFPGC patients has not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…One study described several different treatment options that can delay the progression of HAS, including cisplatin plus uorouracil and epirubicin or irinotecan combined with mitomycin C [23]. Fang et al reported a case of AFPGC patients with liver metastasis who underwent multimodal treatment including surgery, chemotherapy, interventional therapy and sorafenib targeted therapy, with an OS of 30 months [24].…”
Section: Discussionmentioning
confidence: 99%